2016
DOI: 10.1097/anc.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Weight-Based Formula for Neonatal Gastric Tube Insertion Length

Abstract: Further studies comparing accuracy of length/height and weight-based estimations for gastric tube insertion lengths in very preterm and extremely preterm infants are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 11 publications
0
19
0
7
Order By: Relevance
“…The use of the weight-based formula as an auxiliary method to NEMU in GT insertion was described in another study 27 , however, the result was lower than expected, with 16% of tubes being incorrectly positioned (above or near the gastroesophageal junction). The authors suggest that this result is justified by the fact that the formula was not fully incorporated by the nursing team as a measurement strategy.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The use of the weight-based formula as an auxiliary method to NEMU in GT insertion was described in another study 27 , however, the result was lower than expected, with 16% of tubes being incorrectly positioned (above or near the gastroesophageal junction). The authors suggest that this result is justified by the fact that the formula was not fully incorporated by the nursing team as a measurement strategy.…”
Section: Resultsmentioning
confidence: 94%
“…Among the articles that addressed GT measurement, four were observational studies 13 , 18 , 22 , 27 and two were experimental studies 12 , 20 , and were mostly published in nursing journals. With regard to ethical aspects, only one article 12 did not report having submitted the study to ethical appreciation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the result was lower than expected, with incorrect placement in 16% of tubes, i.e., above or near the gastroesophageal junction. The authors suggested this result is justified by the fact that the nursing team did not fully incorporate the formula as a strategy to check the measure- (17) Few studies report the measurement of the tip orifices of the tubes used, although this factor is important to ensure the administration of diet and medications in the gastric cavity. In studies where this value was reported, measurements ranged from 1.5 cm to 3.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…A intubação gastrintestinal é um dos procedimentos mais frequentemente usados na prática assistencial da enfermagem por todo o mundo, sendo indicada para alimentação, descompressão, lavagem e aspiração gástrica, além da administração de medicamentos 5,[7][8][9][10][11] .…”
Section: Revisão De Literaturaunclassified